PEMANFAATAN MINI MENTAL STATE EXAM (MMSE) OLEH DOKTER-DOKTER PUSKESMAS UNTUK DETEKSI DINI GANGGUAN DEMENSIA PADA ORANG TUA LANJUT USIA (LANSIA) DI KABUPATEN BENGKULU UTARA - Suryo Bantolo; Zayadi Zainuddin; Utari Hartati Suryani (Universitas Bengkulu, 2018)
One of the health problems in the elderly are dementia disorder, or better known to laymen as senile. About 5% of 65-70 year old age suffer from dementia and has doubled every 5 years reached 45% at the age of 85 years. The purpose of this activity is to equip doctors of health centers to implement the use of MMSE as a screening tool that is sustainable for the prevention of disorder dementia in the elderly. The methods of these activities by providing direct training to the general practitioners to use the MMSE. Training activities and practice the use of MMSE for clinics doctors in North Bengkulu district has been going smoothly after the expected. It is necessary synergy between health centers, hospitals and health authorities to monitor this activity and follow up on the elderly who experience these dementia. Keywords: Dementia, MMSE, Training